An Interactive Augmented Reality-Based Learning Model for IPAS Oriented Toward Scientific Literacy - Rizki Maulana; Nurhadiansyah Nurhadiansyah (Journal of General Education and Humanities, 2026)
This study investigates the development and implementation of an interactive Augmented Reality (AR)-based learning model for Integrated Science and Social Studies (IPAS) oriented toward scientific literacy. The background highlights the challenges in students’ understanding of abstract concepts and the low scientific literacy levels resulting from the dominance of conventional, low-visualization learning methods. The objective of this study is to develop and evaluate an AR-based learning model that facilitates conceptual understanding and supports scientific literacy in junior high school students. A Research and Development (R&D) approach is employed using a modified Waterfall model comprising analysis, design, implementation, and testing stages. The study also applies an experimental procedure with three learning treatments: printed book-based learning, independent AR-based learning, and a combined approach integrating both methods. Data are collected through documentation of pre-test and post-test results and analyzed using descriptive statistical techniques. The findings reveal that the combined learning approach produces the most significant improvement in students’ learning outcomes, with the average score increasing from 50.1 in the pre-test to 80.4 in the post-test. The results indicate that integrating AR into a structured learning model enhances students’ understanding of abstract concepts and supports the development of scientific literacy. The study concludes that the proposed AR-based learning model provides a more interactive, concrete, and meaningful learning experience and can serve as an effective instructional strategy in IPAS learning at the junior high school level